Latex-mediated synthesis of ZnS nanoparticles: green synthesis approach - Hudlikar, Manish; Joglekar, Shriram; Dhaygude, Mayur; Kodam, Kisan M. (Journal of Nanoparticle Research, 2012)
A low-cost, green synthesis of ZnS nanoparticles is reported using 0.3 % latex solution prepared from Jatropha curcas L. ZnS nanoparticles were characterized by X-ray diffraction, selected area electron diffraction, transmission electron microscopy, energy dispersive analysis of X-rays, UV-vis optical absorption and photoluminescence techniques. Fourier Transform Infrared Spectroscopy was performed to find the role of cyclic peptides namely curcacycline A (an octapeptide), curcacycline B (a nonapeptide) and curcain (an enzyme) as a possible reducing and stabilizing agents present in the latex of J. curcas L. The average size of ZnS nanoparticles was found to be 10 nm. Latex of J. curcas L. itself acts as a source of sulphide (S-2) ions that are donated to Zn ions under present experimental conditions. Source of sulphide (S-2) ions is still unclear, but we speculate that cysteine or thiol residues present in enzyme curcain may be donating these sulphide (S-2) ions.
Keywords: green synthesis; Latex; ZnS nanoparticles

Lipase-mediated hydrolysis of flax seed oil for selective enrichment of alpha-linolenic acid - Rupani, Banin; Kodam, Kisan M.; Gadre, Ramchandra V.; Najafpour, Ghasem D. (European Journal of Lipid Science and Technology, 2012)
Polyunsaturated fatty acids (PUFA) are important ingredients of human diet because of their prominent role in the function of human brain, eye and kidney. alpha-Linolenic acid (ALA), a C18, n-3 PUFA is a precursor of long chain PUFA in humans. Commercial lipases of Candida rugosa, Pseudomonas cepacea, Pseudomonas fluorescens, and Rhizomucor miehei were used for hydrolysis of flax seed oil. Reversed phase high performance liquid chromatography followed by gas chromatography showed that the purified oil contained 12 triacylglycerols (TAGs) with differences in fatty acid compositions. Flax seed oil TAGs contained alpha-linolenic acid (50%) as a major fatty acid while palmitic, oleic, linoleic made up rest of the portion. Among the four commercial lipases C. rugosa has preference for ALA, and that ALA was enriched in free fatty acids. C. rugosa lipase mediated hydrolysis of the TAGs resulted in a fatty acid mixture that was enriched in alpha-linolenic to about 72% yield that could be further enriched to 80% yield by selective removal of saturated fatty acids by urea complexation. Such purified ALA can be used for preparation of ALA-enriched glycerides. Practical applications: This methodology allows purifying ALA from fatty acid mixture obtained from flax seed oil by urea complexation.
Keywords: a-Linolenic acid; Flax seed oil; Lipases; PUFA; Urea complexation